LITERATUR REVIEW : ANALISIS TINGKAT PENCEMARAN UDARA AKIBAT LALU LINTAS KENDARAAN DI INDONESIA - Anggi Pratiwi; Cici Lestari; Zultira Harina Roza; Firdus; Alia Rizki; Muhammad Nasir (KENANGA : Journal of Biological Sciences and Applied Biology, 2024)
Human activities can directly or indirectly cause air quality to drop to a certain level. The increasing growth of a city goes hand in hand with increasing human activities and the increasing number of vehicles in urban areas, resulting in changes in the composition of ambient air quality. The decrease in air quality can disturb and endanger the surrounding environment, especially humans. This research was conducted with a literature study related to air pollution due to transportation activities in regencies and cities in Indonesia. Based on the results of the literature study, it is known that from 16 districts / cities, the most pollutants in air pollution are CO and NO2 and the pollutant with the lowest value is Pb.